Academic libraries and research data management - Juan-José Boté-Vericad; Sharon Healy (Vjesnik Bibliotekara Hrvatske, 2022)
Purpose. Open Science entails research reproducibility, with an emphasis on data sharing and reuse. Hence, research data management (RDM) is an essential asset in research institutions for supporting open science. This study oﬀers a systematic review of the landscape of research data management in academic libraries. It further examines the inﬂuence academic libraries can have if they are involved in the research lifecycle process, and how this beneﬁts research institutions that have started implementing research data management, especially in the data-intensive disciplines.